Optimization of Retention Levels Using the Pentikäinen Method: A Case Study on Unit-Linked Insurance Product - Karin Amelia Safitri; Siti Mahsa Khalilah; Niken Yulia Astuti (UIN Sumatera Utara, 2026)
This study evaluates the adequacy of surplus reinsurance retention for unit-linked insurance products in Indonesia under changing market and regulatory conditions. Using 2024 portfolio statistics of Insurance X, the study applies the Pentikäinen method, which is grounded in ruin theory, to determine model-based retention levels and compare them with the company’s actual retention policy. The analysis incorporates premium income, claim experience, reserve considerations, and security loading assumptions. The results show that the company’s actual retention of IDR 500,000,000 is higher than the retention levels generated by the Pentikäinen model, namely IDR 275,000,000 at 0% loading, IDR 305,000,000 at 10% loading, and IDR 335,000,000 at 20% loading. Simulation results further indicate that lower retention reduces the insurer’s net retained claims and improves financial stability, as reflected in a decline in the loss ratio from 6.75% under the actual retention to 6.12%, 5.95%, and 5.74%, respectively. However, lower retention also increases reinsurance premium cessions, implying a trade-off between risk reduction and cost efficiency. The findings suggest that the retention range of IDR 305,000,000 to IDR 335,000,000 provides a more balanced outcome than both the current retention and the lowest simulated retention. This study contributes to the literature by providing an empirical application of the Pentikäinen method in surplus reinsurance for unit-linked products in Indonesia and offers a more objective basis for retention policy adjustment.